2010
DOI: 10.14210/bjast.v4n1.p1-9
|View full text |Cite
|
Sign up to set email alerts
|

O Clima De Ondas Na Costa Sul De Arraial Do Cabo, Rj: Distribuição De Parâmetros De Onda

Abstract: Ondas de gravidade geradas pelo vento são as principais responsáveis pelo transporte de sedimentos em praias oceânicas. O conhecimento das alturas, dos períodos e das direções das ondas no início da zona de arrebentação, bem como as características geomorfológicas da praia, são fundamentais ao conhecimento da evolução morfológica das mesmas, permitindo, por exemplo, prever respostas a possíveis ações antrópicas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
2
Order By: Relevance
“…In spite of their importance, wave measurements in Brazil are very scarce, and only a few studies assessed regional wave characteristics based on short-term observations (e.g. : CANDELLA, 1997;PEREIRA et al, 2000;ARAÚJO et al, 2003;BENSI et al, 2005). However, with the development of accurate ocean-atmosphere interaction models such as the NOAA WAVEWATCH-III -NWW3 (TOLMAN, 1999), it has become possible to obtain long term time series data from model hindcast.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of their importance, wave measurements in Brazil are very scarce, and only a few studies assessed regional wave characteristics based on short-term observations (e.g. : CANDELLA, 1997;PEREIRA et al, 2000;ARAÚJO et al, 2003;BENSI et al, 2005). However, with the development of accurate ocean-atmosphere interaction models such as the NOAA WAVEWATCH-III -NWW3 (TOLMAN, 1999), it has become possible to obtain long term time series data from model hindcast.…”
Section: Introductionmentioning
confidence: 99%
“…Em outros estudos com participação do mesmo autor, foram analisadas as ondas da região sul da cidade de Arraial do Cabo, que permitiram os resultados de algumas características interessantes como, por exemplo, a altura média das ondas, que na maior parte do tempo variou entre 100 e 200 cm em períodos de 11 a 13 segundos. Um segundo pico de energia veio de ESE a SSE com períodos predominando entre 7 e 9 segundos (PEREIRA; CANDELLA; CARVALHO, 2000).…”
Section: Energia Das Ondasunclassified
“…On the Southern Shelf of Brazil, waves have amplitudes between 1 and 1.5m, periods between 6 and 14s and come mainly from the southeast (Cuchiara et al, 2009). The analysis of 11 years of model data from the operational system WAVEWATCH III showed that, along the Brazilian coast, the energy of the waves decreases from north to south (Pianca et al, 2010). This result reflects the wind regime on the southsoutheastern coast, which is consistently impacted by the passage of cold front systems, with strong winds from the S-SW (Rodrigues et al, 2004;Dominguez, 2006), while on the northeastern coast the trade winds are the main source that generate gravity waves.…”
Section: Introductionmentioning
confidence: 98%
“…At Cabo Frio, for instance, the waves come mainly from the SSE-SSW with periods between 11 and 13s (Pereira et al, 2010). On the Southern Shelf of Brazil, waves have amplitudes between 1 and 1.5m, periods between 6 and 14s and come mainly from the southeast (Cuchiara et al, 2009).…”
Section: Introductionmentioning
confidence: 98%